2012
DOI: 10.1590/s0103-50532012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and phenolic composition of brazilian honeys and their extracts

Abstract: Foram avaliadas as atividades antioxidantes e o conteúdo de polifenóis de cinco méis silvestres e quatro de laranjeira, bem como de seus extratos fenólicos. A identificação e quantificação das substâncias fenólicas foram realizadas por HPLC-DAD (cromatografia líquida de alta eficiência com detecção por arranjo de diodos). A atividade sequestradora de radicais livres, determinada por 2,2-difenil-1-picrilhidrazil (DPPH •) e expressa como CE 50 , variou de 10,81 a 52,64 mg mL-1 para mel e de 6,17 a 52,87 mg mL-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 16 publications
7
31
2
5
Order By: Relevance
“…The levels of phenolic acids are higher than those of flavonoids in these samples. This trend was expected, and was previously observed by Sant'Anna et al 10 and Lianda et al 11 in Brazilian honeys. The results of TF contents obtained for honey extracts were lower than the values previously reported for other Brazilian honeys, 11 which ranged from 12.72 to 76.65 mg GAE 100 g -1 and 0.16 to 5.34 mg QE 100 g -1 .…”
Section: Total Phenolic Content (Tp) and Flavonoid Content (Tf)supporting
confidence: 87%
See 1 more Smart Citation
“…The levels of phenolic acids are higher than those of flavonoids in these samples. This trend was expected, and was previously observed by Sant'Anna et al 10 and Lianda et al 11 in Brazilian honeys. The results of TF contents obtained for honey extracts were lower than the values previously reported for other Brazilian honeys, 11 which ranged from 12.72 to 76.65 mg GAE 100 g -1 and 0.16 to 5.34 mg QE 100 g -1 .…”
Section: Total Phenolic Content (Tp) and Flavonoid Content (Tf)supporting
confidence: 87%
“…This trend was expected, and was previously observed by Sant'Anna et al 10 and Lianda et al 11 in Brazilian honeys. The results of TF contents obtained for honey extracts were lower than the values previously reported for other Brazilian honeys, 11 which ranged from 12.72 to 76.65 mg GAE 100 g -1 and 0.16 to 5.34 mg QE 100 g -1 . The values of TP content obtained by Silva et al 12 for Brazilian melipona honey extracts were also higher than those found in this study.…”
Section: Total Phenolic Content (Tp) and Flavonoid Content (Tf)supporting
confidence: 87%
“…One of the important functions of antioxidants in the living system is preventing the disturbance and functional loss of biological membranes and enzymes by scavenging the free radicals that otherwise induce oxidation of lipids, proteins, and DNA [17]. The antioxidant activity of phenolics is mainly due to their redox properties, which allows them to act as reducing agents [18,19]. To analyse the antioxidant activity of honey and propolis, the analytical methods commonly used refers to the sample's reducing capacity using the FolinCiocalteu or Folin-Denis and ferric reducing antioxidant power (FRAP) tests as well as antiradical activity with the 2,2-diphenyl-1-picryl-hydrazyl (DPPH) radical scavenging assays [4].…”
Section: Introductionmentioning
confidence: 99%
“…Bu değerler, üretilen diğer monofloral ballar ile kıyaslandığında fenolik içeriği açısından kestane > çam > akasya > narenciye> şeklinde bir değerlendirme yapmak müm-kündür ( Tablo 3). 23,26,27,[37][38][39] Çalışma sonuçlarımız diğer ülkelerde çeşitli ballarda yapılan araştırma sonuçları ile karşılaştırıldığında, çam balına ait fenolik içeriğinin yüksek olduğu görülmektedir ( Tablo 3). 23,27,40 Çalışmada, flavonoid içeriği 1,24 ile 8,79 (QE/kg bal) arasında değişkenlik göstermektedir ve ortalama değeri 4,86±0,59 bulunmuştur.…”
Section: Discussionunclassified
“…Çalışma sonuçlarımız, diğer monofloral ballar ile kıyaslandığında flavonoid içeriğinin çam> kestane> akasya> ayçiçeği> narenciye şeklinde bir değere sahip olduğu görünmektedir. 37,38 Diğer ül-kelerde yapılan araştırma sonuçları ile karşılaştırıl-dığında ise türler arası ve bölgesel farklılığa bağlı değişkenlik göstermektedir (Tablo 3). 25,43 Çalışmada total antioksidan aktivitesinin hesaplanması, balın DPPH üzerinde serbest radikal süpü-Örnekler Total flavonoid (mgQE/kg) (min-max) Total fenolik mgGAE/kg) (min-max) Antioksidan, DPPH-sc 50 (mg/ml) (min-max) …”
Section: Discussionunclassified